Status of the immunity of patients with chronic staphylococcus’s pharyngitis - Ognivenko, E; Popov, N (Annals of Mechnikov's Institute, 2020)
Immunomodulatory and immunostimulatory drugs present the greatest interest in treating such patients and the rehabilitation of their immune system. Today, a wide clinical application has Polioksidonium (Petrovax Pharm), which has a wide range of influence on the immune system. There are studies proving the effectiveness of Polioksidonium treatment of inflammatory diseases of the nasal cavity and paranasal sinuses, chronic inflammatory process in pharyngeal plexus. Material and methods We observed 62 patients on chronic staphylococcus’s pharyngitis in age from 21 to 45 years, who were treated in the communal health institution "Kharkiv city hospital № 6". The first group (basic group) amounted to 32 patients, together with anti-inflammatory therapy (topical Decatilen 1 tablet 3 times daily for 7 days, physiotherapy for 5 days, was obtained Polioksidonium (12 mg every 24 hours per os for 10 days). The second group (control group) consisted of 30 patients who received similar therapy without Polioksidonium. Clinical, microbiological, immunological studies were performed before the treatment, at 7 and 30 days after the end of the therapy. As indicators of standards the results of 30 healthy individuals were used. Immunological studies included the determination of the phagocytic activity of neutrophils, their biocidity, opsonizing properties serum titers of antibodies to the causative infectious agents, concentrations of the major classes of immunoglobulins in saliva and serum. Results and discussion. Before the treatment the patients showed complaints to pain and irritation in a throat, feeling of a foreign matter in a throat, dry cough and low-grade fever. Microbiological examination of oropharyngeal secretions ChFh patients revealed a 34 % S. pneumonia, at 24 % - S.aureus. Microbial associations were sown in 45 % of the cases. Immunological studies have shown that patients with chronic staphylococcus’s pharyngitis of increasing concentrations of IgG and mIgA and reducing values sIgA and lysozyme in oropharyngeal secretions. It has also been found that digesting and absorbing capability of bacterial particles neutrophils peripheral blood of patients with ChPh lower than that of healthy individuals. Low phagocytic ability of cell for patients with HF was observed in respect of opsonized autoserum bacteria. In all patients of the main group and the comparison group revealed a significant increase in antibody titer to bacterial etiological factors and common antigenic determinative (CAD) bacteria. High antibody titers were detected for almost all microbes studied. The clinical observations have shown that under the influence of Polioksidonium patients with chronic staphylococcus’s pharyngitis on the 7th day after the treatment has shown a marked decrease or complete disappearance of the major clinical symptoms. All patients receiving Polioksidonium markedly improved overall health. The instrumental examination the 65% of the patients of the main group and the 70% of comparison group on the 7th day after the end of treatment were observed with swelling and hypertrophy of the mucous membrane of the posterior pharyngeal wall. On the 30th day after the end of treatment, 71.8% of the study group patients were without complaints (in the comparison group - 30 % of patients), and their clinical status was characterized by the norm. Pharyngoscope at 22 % of the patients of the main group and at 66% of the patients of the comparison group experienced a slight hypertrophy of the mucous membrane of the posterior pharyngeal wall. Microbiological examination of the main group found in 15,7 % of cases the рresent of pathogens, marked decrease in microbial associations without the appearance of fungal flora and 68% of the pathogenic microflora. In the control group half of the patients (52 %) was sown pathogenic flora, a slight decrease in the amount of microbial associations. Under the effect of Polioksidonium the increase of the secretory IgA and serum immunoglobulins, and lysozyme occurred in the content of oropharyngeal secretions. On the 7th day after the treatment the patients receiving Polioksidonium, had a significant increase in the phagocytic activity of neutrophils and biocide effect, and increase serum opsonizing properties. The autoserum increased both in the absorption capacity of neutrophils and their biocidal effect. Full restoration of the functional activity of phagocytic cells in these patients occurred by 30 days after treatment. To compare the group of patients we have studied that the properties of cells and serum opsonizing properties recovering very slowly and by 30 days were significantly different from the norm. On the 7th and 30th days after the end of the treatment the patients who received Polioksidonium, had an increase in antibody titer to infectious etiologic pathogens and IgG antibodies to CAD bacteria. The patients who did not receive Polioksidonium, such dynamic improvements in humoral immunity was observed. By 30th days after the treatment the patients in a comparison group the antibody titer to infectious etiologic pathogens and their affinity were not significantly changed compared to their values before treatment. The monitoring of patients during the year showed that the main group was not observed recurrence ChFh. They are much less likely than the comparison group was ill patients with acute respiratory infections, which are mild and not accompanied by complications. In the study group acute respiratory infections 2-3 times a year have been reported in 17 % of patients. Patients with ChFh comparison group relapses occurred in 40% of cases, of which 25% of patients - 2-3 times a year, 70% of patients 2-3 times a year suffered acute respiratory illness, which in 23,8% of cases complicated by acute bronchitis, 15% - by acute sinusitis. Conclusions: 1. Polioksidonium stimulates the increase of phagocytic and biocidal activity of white blood cells, the production of high affinity antibodies antimicrobial, increased serum opsonin properties. 2. Using polyoxidoniumdecrease themanifestationsof painandintoxication. 3. Polioksidonium has a positive effect both on the clinical course of chronic pharyngitis and prevention of its recurrence.